(3n-1)(2n-1)=15

Simple and best practice solution for (3n-1)(2n-1)=15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3n-1)(2n-1)=15 equation:


Simplifying
(3n + -1)(2n + -1) = 15

Reorder the terms:
(-1 + 3n)(2n + -1) = 15

Reorder the terms:
(-1 + 3n)(-1 + 2n) = 15

Multiply (-1 + 3n) * (-1 + 2n)
(-1(-1 + 2n) + 3n * (-1 + 2n)) = 15
((-1 * -1 + 2n * -1) + 3n * (-1 + 2n)) = 15
((1 + -2n) + 3n * (-1 + 2n)) = 15
(1 + -2n + (-1 * 3n + 2n * 3n)) = 15
(1 + -2n + (-3n + 6n2)) = 15

Combine like terms: -2n + -3n = -5n
(1 + -5n + 6n2) = 15

Solving
1 + -5n + 6n2 = 15

Solving for variable 'n'.

Reorder the terms:
1 + -15 + -5n + 6n2 = 15 + -15

Combine like terms: 1 + -15 = -14
-14 + -5n + 6n2 = 15 + -15

Combine like terms: 15 + -15 = 0
-14 + -5n + 6n2 = 0

Factor a trinomial.
(-7 + -6n)(2 + -1n) = 0

Subproblem 1

Set the factor '(-7 + -6n)' equal to zero and attempt to solve: Simplifying -7 + -6n = 0 Solving -7 + -6n = 0 Move all terms containing n to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + -6n = 0 + 7 Combine like terms: -7 + 7 = 0 0 + -6n = 0 + 7 -6n = 0 + 7 Combine like terms: 0 + 7 = 7 -6n = 7 Divide each side by '-6'. n = -1.166666667 Simplifying n = -1.166666667

Subproblem 2

Set the factor '(2 + -1n)' equal to zero and attempt to solve: Simplifying 2 + -1n = 0 Solving 2 + -1n = 0 Move all terms containing n to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -1n = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -1n = 0 + -2 -1n = 0 + -2 Combine like terms: 0 + -2 = -2 -1n = -2 Divide each side by '-1'. n = 2 Simplifying n = 2

Solution

n = {-1.166666667, 2}

See similar equations:

| 8x+84=y | | 5x-3y=-72 | | 0.11x+4=8-0.4x | | 0.2x+2.4x=9.1-1.7+2.4x | | 0.45x+0.10(250-x)=49.5 | | 3x+2y+6z=0 | | d/dx(3y-2x=6y-6xy) | | 0.4-4+7-0.9y= | | 12a*12a= | | 12a^2*2= | | 15/12=21/x | | -0.7x=2.8 | | n(n+2)+n+2=12 | | 3.6g+2=1.6g+12 | | 12w=10+9 | | 2(n-1)(2n-1)+3n-1(n+1)=21 | | 6n+2=398 | | 8a+10a=10 | | 5x+18-4x=-3+(-10) | | 4s+6c=45 | | 5n-7=12 | | -81=27 | | 3+c=4+1 | | 5n-7=14 | | 5n-7=10 | | 3s+5c=34 | | 4(8x+5)-10(5x+2)= | | 5n-7=40 | | (2+4n)+(9+2y)= | | 12=4+v | | 6(15-6x)+11(4x-8)= | | -70=14x |

Equations solver categories